Estudio del tiempo de vida útil de una bebida láctea simbiótica, elaborada empleando Lactobacillus rhamnosus, Bifidobacterium s. p. y pectina cítrica - Mendoza Intriago, Luiggi Adrián (2022)
To analyze the effect of of L. rhamnosus and Bifidobacterium s. p. and citrus pectin in the shelf life time (SLT) of a fermented milk beverage, two different culture doses were used, with and without citrus pectin. L. bulgaricus and S. thermophilus, a culture commonly used in the production of yogurt, they were also used as a comparison. Both cultures were used at doses of 0.006 % and 0.012 % and incubated at their optimum activity temperature (44 and 37 ºC, respectively), obtaining a total of 8 treatments (T1 to T8). The analysis of pathogenic bacteria (total coliforms) and of viable probiotics, carried out at intervals of 5 days during storage (8 ºC), allowed, respectively, to predict the shelf life of the beverage, and the survival time of probiotics, using a kinetic model of order one. At the end of storage, all the beverages produced showed amounts of probiotics greater than 107 CFU/mL, absence of E. coli, total coliforms between 6 to 10 CFU/mL, molds and yeasts in the range of 12 to 28 CFU/mL, according to the requirements of the regulations. The beverages made with citrus pectin exhibited a longer shelf life, and also a longer probiotic survival time, with a lower value of the kinetic constant, than for the beverages prepared without this prebiotic. The longest equal shelf life (37 days) was observed with the use of L. rhamnosus and Bifidobacterium s. p. at a dose of 0.012 % w/v and citrus pectin 0.34 % (T8), and the longest survival time of probiotics (161 days), was also observed in the presence of pectin at the indicated dose, when using L. bulgaricus and S. thermophilus at 0.006 % (T2) (p<0.05). L. rhamnosus and Bifidobacterium s. p. in treatments with citrus pectin, they also reached quite high survival times, with values of 105 and 152 days, when used at low (0.006 %) and high (0.012 %) doses (T6 and T8), respectively. The results observed regarding the use of L. rhamnosus and Bifidobacterium s. p. and citrus pectin, on the useful life and survival of viable probiotics, have not yet been reported in other studies, and may serve as a great contribution to achieve technological or functional advantages in the development of new symbiotic foods. Keywords: Milk beverage, L. bulgaricus, S. thermophilus, L. rhamnosus, Bifidobacterium, citrus pectin, shelf life.